An efficient simulation and analysis method of moire patterns in display systems - Byun, Seok-Joo; Byun, Seok Yong; Lee, Jangkyo; Kim, Won Mok; Kim, Han-Pil; Jeon, Min Yong; Lee, Taek-Sung (OPTICAL SOC AMER, 2014)
A precise and fast computational method for the simulation and analysis of moire patterns is proposed. This new algorithm is based on convolution with superposition of the intensity profile which is transmitted from the optical layers and the point spread function. The computational time is shown to be much faster than that of the ray-tracing algorithm because the new algorithm does not involve a massive calculation. Also, information on the moire pitch can be extracted directly from the sampling data of the moire patterns. (C) 2014 Optical Society of America
Keywords: MINIMIZATION; ARRAY; FILM